(untitled) - Kapoor, Jack R. (New York, 2012)
Content provides many financial planning tools using a step-by-step approach to help students identify and evaluate choices as well as understand the consequences of decisions in terms of opportunity costs. Managing money in order to obtain freedom from financial worries – that’s what the 10th edition of Personal Finance is all about! Connect is the only integrated learning system that empowers students by continuously adapting to deliver precisely what they need, when they need it, and how they need it, so that your class time is more engaging and effective.
Keywords: Finance, Personal,Tài chính, cá nhân